Apprising Constitutional Amendment in Ethiopia: Vexing Questions and Qualms - Eshetu, Zelalem Degifie (Bahir Dar University Journal of Law, 2022)
The Federal Democratic Republic of Ethiopia (FDRE) Constitution sets forth procedures to guide actions concerning constitutional amendments. This study examines the nature of amendment procedures adopted under the Ethiopian legal system based on comparative and analytical approaches and finds that they are not clear and sufficient enough to guide the process.Moreover, the study demonstrates that the amending provisions of the Constitution has left many issues pertaining to constitutional amendments perplexing and unanswered, which in turn creates uncertainty in the process of formal constitutional changes. Finally the study strongly recommends the amending clauses of the FDRE Constitution to be revisited and a detailed law dealing with constitutional amendment procedures to be enacted, in order to correct the gaps on the issues of initiation, ratification, publication, timeline for actions, public participation and reversals.